PENERAPAN RESPONSIBILITAS DAN TRANSPARANSI LAYANAN PUBLIK ( Sebuah Kajian Ilmu Administrasi) - Astri Dwi S; Sri Indarti; Novliza Eka Patrisia (UNIVED PRESS, Universitas Dehasen Bengkulu, 2020)
The number of complaints and complaints from the public on government services, both directly and indirectly, or through the mass media, such as complaints about convoluted service procedures, lack of certainty in the period of settlement, the amount of costs to be incurred, the absence of requirements transparency, and the attitude of officers or employees who are less responsive is a program faced in public services. The formulation of the problem in this study is how the application of responsibility and transparency in the Bengkulu Province Regional Financial Management Agency To obtain answers to the research problems, researchers used qualitative research methods. From the results of the study it was found that Transparency in the Office of the Regional Financial Management Agency of Bengkulu Province has implemented the principle of transparency to assist in the provision of services to the public that is helping to facilitate payments. The application of the principle of responsibility in the Office of the Regional Financial Management Agency of Bengkulu Province can be seen from the extent of the implementation of the activities of the Office of the Regional Financial Management Agency of Bengkulu Province in carrying out its duties and responsibilities to the community, for example with the satisfaction of service to the community, the constraints obtained in this responsibility, namely the service given is not satisfactory for the community because it has not yet completed the office facilities of the Bengkulu Province Regional Financial Management Office in accordance with applicable principles. Keywords: responsibilitas, transparansi, layanan publik